Alter egos : Hillary Clinton, Barack Obama, and the twilight struggle over American power - Landler, Mark (New York Random House, 2016)
Alter Egos In the annals of American statecraft, theirs was a most unlikely alliance. Clinton, daughter of an anticommunist father, was raised in the Republican suburbs of Chicago in the aftermath of World War II, nourishing an unshakable belief in the United States as a force for good in distant lands. Obama, an itinerant child of the 1970s, was raised by a single mother in Indonesia and Hawaii, suspended
Include index and Bibliography
Keywords: Obama, Barack. -- Clinton, Hillary Rodham. -- Diplomatic relations